Analysis of Various Feedstocks for Biogas Production Using Portable Digester for Sustainable Energy in Jigawa State - Salisu I. Kunya; Ibrahim Isah; Sulaiman Zakari (International Journal of Scientific Research and Innovative Studies, 2025)
A number of experiments were conducted as part of the study to examine the output of biogas from the digestion of horse dung, poultry droppings, and cattle manure with the intent to generate energy for heating needs. As the anaerobic digestion (AD) process of producing biogas from manure has several benefits, such as the creation of jobs, reduces the need for firewood or fossil fuels, and produces less indoor smoke and greenhouse gas emissions than other fuel types used in developing nations. Initially, the slurry were prepared and put into digesters, and the biogas produced were analyzed. The results demonstrated that anaerobic digestion of these feedstock successfully operate with maximum biogas yield of respectively for cow, poultry dropping and horse dung respectively. The finding shows that by comparing the samples production yield, we have seen that the daily and cumulative biogas yield from cow dung is higher with peak values of respectively. A pH results illustrated that a value close or equal to 7 is a favorable condition for methanogeneis. As such, small-scale biogas digesters can be a very useful manure management tool and may help reduce global warming impacts if used appropriately. Key words: Biogas, Energy, Cow dung, Horse dung, Poultry dropping. Received Date: February25, 2024 Accepted Date: March 18, 2025 Published Date: April 01, 2025 Available Online at https://www.ijsrisjournal.com/index.php/ojsfiles/article/view/359 https://doi.org/10.5281/zenodo.15121718